Measuring Progress in Equitable Urban Sustainability: Six Key Questions from European Cities - Lucinda Cash-Gibson; Ferran Muntané; Mary Sheehan; Júlia Tena Mensa; Joan Benach (Urban Science)
There is mounting evidence and concern that humanity is failing to equitably meet social needs while overshooting the Earth’s ecological boundaries. Efforts to monitor progress towards equitable urban sustainability have expanded significantly over the years; however, challenges remain in comprehensively assessing and comparing the progress made in different settings. To stimulate critical thinking and guide capacity-building efforts, we assessed the main dimensions and indicators used to monitor urban sustainability and equity in a selection of European cities. We analysed city reports to identify major recurring underlying themes, which we framed as guiding questions, and suggested areas for further development. The purpose was not to highlight the strengths and limitations of specific cities’ efforts. Our critical assessment identified several areas that require attention: the need for the more explicit use of theories or conceptual frameworks to select dimensions and indicators and to frame problems (and subsequently to guide intervention design); the standardisation of indicators; and improved data availability, reliability, and disaggregation to support data capturing, reporting, and comparability across settings. Despite meaningful progress, further efforts are needed to strengthen cities’ capacities to measure, monitor, and report on equitable urban sustainability. These efforts should be complemented with educational initiatives to foster the socio-cultural and behavioural changes necessary to achieve more equitable, sustainable, and healthy urban environments.